9 The Statutes at Large of South Carolina: Containing the Acts Relating to Roads, Bridges and Ferries, With an Appendix, Containing the Militia Acts Prior to 1794, at 358 (David J. McCord ed., 1841) - (:unkn) unknown (My University, 1792)
"[A]ll free negroes and Indians, (nations of Indians in amity with the State excepted,) Moors, mulattoes and mestizoes, between the ages of eighteen and forty-five, shall be obliged to serve in the said militia.
Keywords: MILITIAS; ENSLAVED PERSONS AND OTHER MINORITIES